Effects of Deposition Potentials on the Morphology and Structure of Iron-Based Films on Carbon Steel Substrate in an Alkaline Solution. (18th January 2016) - Jeon, Soon-Hyeok; Song, Geun-Dong; Hur, Do Haeng
Abstract : The purpose of this work is to investigate the effect of electrochemical deposition potential on the morphology and structure of iron-based films on the carbon steel in an alkaline Fe(III)-triethanolamine solution. The deposition potentials were controlled in the range from −1.05 to −1.23 V S C E for 1800 s at 80°C. Total amount of electric charge for electrodeposition process was increased with increasing deposition potential in negative direction. Pure magnetite films with a columnar and defect-free structure were deposited in the potential range from −1.05 V S C E to −1.11 V S C E . However, petal-like magnetite film containing ferrihydrite and iron was formed at −1.17 V S C E . At more negative potential of −1.23 V S C E, two distinct layers were observed: a porous outer layer containing ferrihydrite and goethite and a compact inner layer consisting of columnar metallic iron. In the potential range from −1.05 to −1.11 V S C E, the pure magnetite films gradually increased the thickness and decreased the surface roughness with an increase of the overpotential. The magnetite film deposited at −1.11 V S C E showed the most thick layer and smooth surface state.